Analisis Perlakuan Akuntansi Hubungan Kantor Pusat dan Kantor Cabang Pada Usaha Papabendonut Coffee & Eatery - Arini Nur Arista; Abdul Aziz Ramadhan; Rani Asupa; Ratna Septina; Carmidah Carmidah (Jurnal Riset Akuntansi, 2024)
This research examines the analysis of the accounting treatment of head office and branch office relationships at Papabendonuts Coffee & Eatery. The purpose of this study is to determine how the implementation of the accounting relationship treatment between the head office and branch offices of Papabendonuts Coffee & Eatery. Through interviews with the shopkeeper of the Papabendonuts Coffee & Eatery branch office located in Mulyojati, West Metro, it was found that the accounting system used in this business uses a centralized system with the implementation of financial statements, bookkeeping at branch and head offices, production authority, merchandise collection, allocation of employee rights costs, recording assets or recording profit and loss. From these implementations, it was found that Papabendonuts Coffee & Eatery has 75% conformity in the implementation of accounting relationships between the head office and branch offices related to the centralization system. The results of this study indicate that Papabendonuts Coffee & Eatery is almost in accordance with the existing centralization system in the accounting relationship between the head office and branch offices.